Gender and Discipline: Intensifier Variation in Academic Lectures - Liu, Chen-Yu (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2019)
Many studies have explored differences in the use of intensifiers by people of different genders, but few have focused on additional compounding variables that may affect gendered intensifier use. This study thus explored the effects of academics’ gender and subject area on intensifier use in their lectures, as well as the interactions between these two variables. Significant differences were found in the use of intensifiers between genders and between academic disciplines, with male lecturers using significantly more intensifiers than female ones did, and significantly fewer intensifiers occurring in the hard sciences than the soft ones. Of the two variables, discipline was more influential on intensifier variation than gender was. The interaction data, meanwhile, indicated that although male lecturers in both disciplinary groups used intensifiers frequently, their language behaviors were affected far more by the norms of the lecture genre than by discipline. The female lecturers’ intensifier usage, on the other hand, was substantially influenced by both gender and discipline. Taken as a whole, these findings reveal that, although gender is undeniably an important factor in it, intensifier variation is more likely to be explicated through research on the interactive effects of gender and other variables.